Governance quality and trade performance in Sub-Saharan Africa - Simplice Asongu; Nicholas M. Odhiambo (African Governance and Development Institute (AGDI), 2023)
In this study, nexuses between governance and trade performance in terms of natural resource rents are assessed in 44 sub-Saharan African countries. The empirical evidence is based on Tobit regressions. The findings show that political governance (entailing 'voice & accountability' and political stability) and institutional governance (consisting of the rule of law and corruption control) have a negative effect on trade performance. The findings are consistent with the perspective that resources rents are linked to inefficiencies in governance which are further detrimental to trade performance within the remit of natural resource rents on the one hand and, on the other, the premise of the prevailing weak institutions in the region less likely to boost trade performance.
Keywords: H10; Q20; Q30; O11; O55; 330; Natural Resources; Economic Growth; Governance; Sub-Saharan Africa